THE EFFECT OF THE ALPHABET MYSTERY BOX MEDIA ON ENHANCING BEGINNING READING SKILLS IN EARLY CHILDHOOD - Lili, Waode; Hayati, Nur (Ridwan Institute, 2024)
The aim of this study is to investigate the effect of the use of the alphabet mystery box media on early reading skills in early childhood. A literature review was conducted using Google Scholar, Google Search, and ResearchGate. A total of 13 peer-reviewed publications, dated between 2015 and 2024, were included in the review, covering studies in both English and Indonesian. The data analysis utilized content analysis to examine findings related to the Alphabet Mystery Box media and its influence on early childhood reading skills, contextualized within relevant theories and previous research. The results of the study show that the ability to read early through the using of alphabet box media for early childhood has a significant impact on early literacy skills. The use of